Ecclesiastical Jurisdiction in Medieval East Central Europe - Balogh, Elemér (Lectures on East Central European Legal History, 2022)
To interpret the legal–geographical dimension of the subject indicated in the title, it is necessary to know that medieval Europe was divided into north–south, roughly as the countries north and south of the Alps. The term ‘Central and Eastern Europe’ is a modern concept that cannot simply be projected back to the Middle Ages. The legal institutions discussed in this chapter have affected the territories of present-day Bavaria, Austria, Slovakia, Slovenia, Croatia, Serbia, and Poland, to a greater or lesser extent. In terms of the medieval ecclesiastical judiciary, this area encompassed both European legal regions, as in the German and Polish territories, the northern type of official judiciary prevailed, while the procedure utilized in the Kingdom of Hungary’s ecclesiastical court can be classified as the southern vicarian judiciary. It is important to emphasize, however, that a number of combined elements from the two judging models can also be detected, and I will elaborate on these features in detail in this chapter. The ecclesiastical judiciary focused on the dioceses, so organizational and jurisdictional rules are included in its main elements in the study. The more detailed section of the Bavarian judiciary presents all important litigants. When discussing institutions in Poland and Hungary, I also tried to highlight the parallels and differences that can be related to each other, and thus, the chapterengages in a comparative discussion of the institutions of ecclesiastical justice in Central and EasternEurope, as promised in the title.KEYWORDS: Bavaria, Poland, Hungary, bishop, archbishop, consistorium, officialis, vicarius, canon law, Roman law, customary law, Tripartitum, iudex delegatus, iurisperiti, assessores, procuratores, notaries, privilegium fori, Regestrum Varadinense, doctores decretorum, mandatum transmissionale.